Public goods, redistribution and rent seeking - Tullock, Gordon (Locke Institute, 2005)
Economists frequently justify government as dealing with externalities, which it certainly does. Gordon Tullock looks at governmental activity that internalises such externalities in this new, original work. However, government can also create. Many standard government activities such as road building, war and internal policing were originally introduced by monarchical governments for the benefit of the monarch and not to eliminate externalities